Fragments Synthesis of A. baumannii ATCC 17961 O-Antigen - Li, Xinxin; Duan, Liangshen; Liu, Deyong; Qi, Jianying; Wang, Liming; Zhang, Qingju (Synlett, 2024)
Acinetobacter baumannii can cause many diseases including septicemia, pneumonia, meningitis, soft tissue, and urinary tract infections. Herein, we described the synthesis of one trisaccharide and two tetrasaccharide fragments derived from A. baumannii ATCC 17961 O-antigen that can be used for screening novel glyco-epitopes and for developing a synthetic carbohydrate-based vaccine against A. baumannii infection. The overall yields for the synthesis of the desired trisaccharide 1, tetrasaccharide 2, and tetrasaccharide 3 are 26.8% (8 steps), 21.6% (9 steps), and 24.5% (6 steps), respectively.
Keywords: Acinetobacter baumannii 17961; oligosaccharides; synthesis; glyco-epitopes; carbohydrate-based vaccines